Formal properties and characteristics of Malay rhythmic reduplication - Sharum, Mohd Yunus; Zainon Hamzah, Zaitul Azma; Abdul Wahab, Mohd Rohaizat; Ismail, Mat Rofa (Elsevier, 2010)
Reduplication is a process of Malay word formation. Generally it can be divided into full, partial and rhythmic reduplication. Another set is the undefined group which is called free-form reduplication. Lexically, the rhythmic reduplication is systematically formed as some of its processes had been able to be identified. The semantical aspect of reduplication is to create ‘multiplicity’, ‘repetition’, ‘concentration’ and ‘variety’. Of these, the rhythmic reduplication is specialized with the latter. Functionally, rhythmic reduplication tends to diversify a set where others may just perform multiplication. Our analysis shows that rhythmic reduplication does exist with purpose. Its systematic formation and usage shows that Malay language had its own device to classify things which rigorously describe different sets of object or their properties.